Cultural competence of undergraduate student nurses: a multicenter study - Sagarra Romero, Lucía; Ramón Arbués, Enrique; Huércanos Esparza, Isabel; Kalkan, Indrani; Kömürcü, Nuran; Vanceulebroeck, Valérie; Dehaes, Shana; Coelho, Margarida; Casa Nova, Antonio; Antón Solanas, Isabel (My University, 2024)
Objective: to evaluate the level of cultural competence of an undergraduate nursing students’ population from four European higher education institutions. Method: a total of 168 nursing students from four different countries were included in our study. The study methodology involved a cross-sectional assessment of cultural competence among undergraduate nursing students from four European universities. Data collection included sociodemographic variables, as well as the following validated tools: the Intercultural Sensitivity Scale, the Cultural Competence Assessment Tool (student version) and the Cultural Awareness Scale. Results: our results indicated that students demonstrated a high level of intercultural sensitivity but a moderate level of cultural competence and cultural awareness. Variations existed among students from different countries, suggesting potential differences in educational approaches. Despite expectations that higher-level students would exhibit greater cultural competence, no significant differences were found by year of study, indicating a lack of effective integration of cultural competence into nursing curricula. Conclusion: nurse educators should consider the students’ cultural competence before designing related study programmes. Training programmes related to cultural competence should include elements which have been associated with enhanced cultural competence, including language skills, cultural encounter, and opportunities for internationalisation.

Objetivo: evaluar el nivel de competencia cultural de una población de estudiantes de pregrado en enfermería de cuatro instituciones europeas de educación superior. Método: en nuestro estudio se incluyeron en total 168 estudiantes de enfermería de cuatro países diferentes. La metodología de estudio implicó una evaluación transversal de la competencia cultural de los estudiantes de pregrado en enfermería de cuatro universidades europeas. La recolección de datos incluyó variables sociodemográficas y las siguientes herramientas validadas: la Escala de Sensibilidad Intercultural, la Herramienta de Evaluación de la Competencia Cultural (versión para estudiantes) y la Escala de Conciencia Cultural. Resultados: los estudiantes demostraron un alto nivel de sensibilidad intercultural pero un nivel moderado de competencia y conciencia cultural. Hubo variaciones entre los estudiantes de diferentes países, lo que sugiere posibles diferencias en los enfoques educativos. A pesar de que se esperaba que los estudiantes de educación superior tuvieran mayor competencia cultural, no se encontraron diferencias significativas por año de estudio, lo que indica que la competencia cultural no se incluye de forma efectiva en los planes de estudio de las carreras de pregrado en enfermería. Conclusión: los educadores de enfermería deben considerar la competencia cultural de los estudiantes antes de diseñar programas de estudio relacionados con la misma. Los programas de formación relacionados con la competencia cultural deben incluir elementos que se hayan asociado con una mayor competencia cultural, eso incluye habilidades lingüísticas, encuentros culturales y oportunidades de internacionalización.

Objetivo: avaliar o nível de competência cultural de uma população de estudantes de graduação em enfermagem de quatro instituições europeias de ensino superior. Método: um total de 168 estudantes de enfermagem de quatro países diferentes foram incluídos em nosso estudo. A metodologia do estudo envolveu uma avaliação transversal da competência cultural entre estudantes de graduação em enfermagem de quatro universidades europeias. A coleta de dados incluiu variáveis sociodemográficas, bem como as seguintes ferramentas validadas: Escala de Sensibilidade Intercultural, Ferramenta de Avaliação de Competência Cultural (versão do aluno) e Escala de Consciência Cultural. Resultados: nossos resultados indicaram que os alunos demonstraram um alto nível de sensibilidade intercultural, mas um nível moderado de competência e consciência cultural. Houve variações entre os alunos de diferentes países, o que sugere possíveis diferenças nas abordagens educacionais. Apesar das expectativas de que os alunos de nível superior apresentariam maior competência cultural, não foram encontradas diferenças significativas por ano de estudo, indicando uma falta de integração eficaz da competência cultural nos currículos de enfermagem. Conclusão: os educadores de enfermagem devem considerar a competência cultural dos alunos antes de elaborar programas de estudo relacionados. Os programas de treinamento relacionados à competência cultural devem incluir elementos que tenham sido associados a uma maior competência cultural, incluindo habilidades linguísticas, encontros culturais e oportunidades de internacionalização.
Competência cultural de estudantes de graduação em enfermagem: um estudo multicêntrico
Competencia cultural de estudiantes de pregrado en enfermería: estudio multicéntrico
Keywords: Transcultural Nursing; Cultural Competency; Culturally Competent Care; Nursing Education; Nursing Students; Cross-Sectional Studies; Enfermería Transcultural; Competencia Cultural; Asistencia Sanitaria Culturalmente Competente; Educación en Enfermería; Estudiantes de Enfermería; Estudios Transversales; Enfermagem Transcultural; Competência Cultural; Assistência à Saúde Culturalmente Competente; Educação em Enfermagem; Estudantes de Enfermagem; Estudos Transversais